A 600 kb deletion syndrome at 16p11.2 leads to energy imbalance and neuropsychiatric disorders. Issue 10 (10th October 2012) - Zufferey, Flore; Sherr, Elliott H; Beckmann, Noam D; Hanson, Ellen; Maillard, Anne M; Hippolyte, Loyse; Macé, Aurélien; Ferrari, Carina; Kutalik, Zoltán; Andrieux, Joris; Aylward, Elizabeth; Barker, Mandy; et al.
Abstract : Background: The recurrent ∼600 kb 16p11.2 BP4-BP5 deletion is among the most frequent known genetic aetiologies of autism spectrum disorder (ASD) and related neurodevelopmental disorders. Objective: To define the medical, neuropsychological, and behavioural phenotypes in carriers of this deletion. Methods: We collected clinical data on 285 deletion carriers and performed detailed evaluations on 72 carriers and 68 intrafamilial non-carrier controls. Results: When compared to intrafamilial controls, full scale intelligence quotient (FSIQ) is two standard deviations lower in carriers, and there is no difference between carriers referred for neurodevelopmental disorders and carriers identified through cascade family testing. Verbal IQ (mean 74) is lower than non-verbal IQ (mean 83) and a majority of carriers require speech therapy. Over 80% of individuals exhibit psychiatric disorders including ASD, which is present in 15% of the paediatric carriers. Increase in head circumference (HC) during infancy is similar to the HC and brain growth patterns observed in idiopathic ASD. Obesity, a major comorbidity present in 50% of the carriers by the age of 7 years, does not correlate with FSIQ or any behavioural trait. Seizures are present in 24% of carriers and occur independently of other symptoms. Malformations are infrequently found, confirming only a few of the previously reported associations. Conclusions: The 16p11.2 deletion impacts in a quantitative and independent manner FSIQ, behaviour and body mass index, possibly through direct influences on neural circuitry. Although non-specific, these features are clinically significant and reproducible. Lastly, this study demonstrates the necessity of studying large patient cohorts ascertained through multiple methods to characterise the clinical consequences of rare variants involved in common diseases.